Regulation of Ku-DNA Association by Yku70 C-terminal Tail and SUMO Modification - Hang, Lisa E. (American Society for Biochemistry and Molecular Biology, 2014)
The Ku70-Ku80 ring complex encloses DNA ends to facilitate telomere maintenance and DNA break repair. Many studies focus on the ring-forming regions of subunits Ku70 and Ku80. Less is known about the Ku70 C-terminal tail, which lies outside the ring. Our results suggest that this region is responsible for dynamic sumoylation of Yku70 upon DNA association in budding yeast. Mutating a cluster of five lysines in this region largely eliminates Yku70 sumoylation. Chromatin immunoprecipitation analyses show that yku70 mutants with these lysines replaced by arginines exhibit reduced Ku-DNA association at both telomeres and internal DNA breaks. Consistent with this physical evidence, Yku70 sumoylation deficiency is associated with impaired ability to block DNA end resection and suppression of multiple defects caused by inefficient resection. Correlating with these, yku70 mutants with reduced sumoylation levels exhibit shorter telomeres, increased G overhang levels, and altered levels of non-homologous end joining. We also show that diminution of sumoylation does not affect Yku70 protein levels or its interactions with protein and RNA partners. These results suggest a model whereby Yku70 sumoylation upon DNA association strengthens Ku-DNA interaction to promote multiple functions of Ku.